2018
DOI: 10.3390/nano8060373
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for the Self-Assembly of Poly(Ethylene Glycol)–Poly(Lactic Acid) (PEG-PLA) into Polymersomes: Beyond the Theoretical Paradigms

Abstract: Polymersomes (PL), vesicles formed by self-assembly of amphiphilic block copolymers, have been described as promising nanosystems for drug delivery, especially of biomolecules. The film hydration method (FH) is widely used for PL preparation, however, it often requires long hydration times and commonly results in broad size distribution. In this work, we describe the challenges of the self-assembly of poly (ethylene glycol)-poly(lactic acid) (PEG-PLA) into PL by FH exploring different hydrophilic volume fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
1
19
0
2
Order By: Relevance
“…Another major issue associated with the ASNase nanotechnological development is the scale-up process and its inherent challenges (Paliwal et al, 2014). Several methods are available at laboratory scale to produce nanostructures for protein drug delivery, but scale up demands high efficiency, a fast and continuous process and adequate methods for thermolabile proteins like ASNase (e.g., cold homogenization process) (Paliwal et al, 2014; Pachioni-Vasconcelos et al, 2016; Apolinário et al, 2018). Furthermore, solvent free processes and reduced shear stress are preferable to avoid ASNase denaturation and/or aggregation.…”
Section: L-asparaginase Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another major issue associated with the ASNase nanotechnological development is the scale-up process and its inherent challenges (Paliwal et al, 2014). Several methods are available at laboratory scale to produce nanostructures for protein drug delivery, but scale up demands high efficiency, a fast and continuous process and adequate methods for thermolabile proteins like ASNase (e.g., cold homogenization process) (Paliwal et al, 2014; Pachioni-Vasconcelos et al, 2016; Apolinário et al, 2018). Furthermore, solvent free processes and reduced shear stress are preferable to avoid ASNase denaturation and/or aggregation.…”
Section: L-asparaginase Formulationmentioning
confidence: 99%
“…Furthermore, solvent free processes and reduced shear stress are preferable to avoid ASNase denaturation and/or aggregation. Lack of control of nanocarrier size and polydispersity are two common pitfalls for some of the production methods employed in small scale such as film hydration (Apolinário et al, 2018). To solve this problem, size exclusion chromatography can be added as a nanostructure purification step (Wang et al, 2010).…”
Section: L-asparaginase Formulationmentioning
confidence: 99%
“…Figure 7 is the TEM photograph of sc-PLAG-5%, and other sc-PLAG samples also possessed similar morphology. The microspheres with a diameter of about 200 nm and the aggregation of microspheres could be observed [43]. In sc-PLAG, the formation of microspheres could be induced by the stereocomplexation of enantiomeric PLA units and the amphiphilicity due to glucose residues and lactic acid units, which indicated that the hydrophobic PLA units likely spontaneously gathered in the center of microspheres to form The results of POM showed that a proper amount of glucose groups would play the role of heterogeneous nucleation agent and improve the crystallization rate of PLA stereocomplex, while a small amount or an excess glucose group could destroy the ordered arrangement of lactic acid units to reduce the regularity of SC.…”
Section: Pom Analysis Of Crystal Morphologymentioning
confidence: 97%
“…Para copolímeros com porção hidrofílica formada por PEG, pode--se ainda inferir o tipo de nanoestrutura formada a partir do parâmetro f (0 < f < 1) e que representa o volume da fração hidrofílica, como descrito na Tabela 2 adaptada de Apolinário et al 41 Os polimerossomas (Figura 4) são elaborados pelos mesmos métodos usados para elaboração de lipossomas na maioria das vezes, mas em razão das características físico-químicas diferenciadas de alguns polímeros, como alta temperatura de transição vítrea que dificulta a extrusão, 42 apresentam algumas limitações, como trabalhos que relatam tempo de hidratação do filme de um mês para que ocorra a formação destas vesículas. 43 Às vezes, há a necessidade de técnicas específicas para encapsulação, como a eletroporação descrita por Wang et al, 44 que consiste na formação provisória de poros na bicamada destas vesículas, permitindo a encapsulação de moléculas grandes, como proteínas terapêuticas.…”
Section: Polimerossomas E Micelas Poliméricasunclassified